Hubungan Karakteristik Pasien Hipertensi Dengan Perilaku Pencegahan Covid-19 Di Pelayanan Rawat Jalan Rumah Sakit Panti Rahayu Yogyakarta - Lola Panggah Pertiwi, Hedwigis; Subiyanto, Paulus; Ratnawati, Emmelia (STIKes Panti Rapih, 2023)
ABSTRAC Background: Coronavirus disease (COVID-19) is an infectious disease caused by a new type of coronavirus and became an outbreak in Wuhan, China, in December 2019. Hypertension patients are the highest comorbidities because it will complicate the patient's condition. COVID-19 such as wearing masks, washing hands, maintaining distance and much more. Objective: To determine the relationship of characteristics of hypertension patients (age, gender, education, occupation) with the prevention behavior of COVID-19 transmission in outpatient services Panti Rahayu Hospital Yogyakarta. Methods: The method used is descriptive cross sectional with sampling accidental sampling technique and obtained by 32 respondents. The research instrument which used was questioner developed by the researcher and has been tested for validity, reliability. Results: The results of data analysis, there is no relationship between the factors of age (P value: 0.170), gender (P value: 1.000), education (P value: 0.567) and employment (P value: 0.433) with Covid-19 prevention behavior in out patient Panti Rahayu Hospital, Yogyakarta. Conculsion: From the results of the study, it was concluded that there is no relationship between the characteristics of hypertension patients and the prevention behavior of COVID-19 transmission. Hypertension patients are obliged to implement preventive behaviors for the transmission of COVID-19. Keywords: hypertension, prevention of COVID-19